2005
DOI: 10.1371/journal.pmed.0020240
|View full text |Cite
|
Sign up to set email alerts
|

Croup Is Associated with the Novel Coronavirus NL63

Abstract: BackgroundThe clinical relevance of infections with the novel human coronavirus NL63 (HCoV-NL63) has not been investigated systematically. We therefore determined its association with disease in young children with lower respiratory tract infection (LRTI).Methods and FindingsNine hundred forty-nine samples of nasopharyngeal secretions from children under 3 y of age with LRTIs were analysed by a quantitative HCoV-NL63-specific real-time PCR. The samples had been collected from hospitalised patients and outpatie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
242
4
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 263 publications
(266 citation statements)
references
References 20 publications
9
242
4
11
Order By: Relevance
“…Interestingly, a large study of pediatric patients in Europe found that HCoV-NL63 infection is associated with croup. 9 Thus, although HCoV-NL63 is likely a common respiratory infection in children, we and others found no association with acute KD.…”
Section: Resultscontrasting
confidence: 67%
“…Interestingly, a large study of pediatric patients in Europe found that HCoV-NL63 infection is associated with croup. 9 Thus, although HCoV-NL63 is likely a common respiratory infection in children, we and others found no association with acute KD.…”
Section: Resultscontrasting
confidence: 67%
“…Since then, two additional human coronaviruses, HCoV-NL63 (NL63) and HCoV-HKU1, have been identified (van der Hoek et al, 2004;Woo et al, 2005). NL63 has been found to be associated with diseases in the upper and lower respiratory tracts, such as bronchiolitis, conjunctivitis, croup and pneumonia in young children and immunocompromised adults (Arden et al, 2005;Bastien et al, 2005;Ebihara et al, 2005;Gerna et al, 2006;Kaiser et al, 2005;van der Hoek et al, 2005. So far, NL63 infections have been reported in 12 countries across Europe, Asia and North America, indicating that it is circulating among the human population worldwide (Arden et al, 2005;Bastien et al, 2005;Han et al, 2007;Koetz et al, 2006;Lau et al, 2006;Suzuki et al, 2005;Vabret et al, 2005).…”
mentioning
confidence: 99%
“…H uman respiratory syncytial virus (HRSV), human metapneumovirus (HMPV), parainfluenzavirus, coronavirus, and adenovirus are commonly detected viruses in children with acute lower respiratory tract infections (LRTI) (1)(2)(3)(4)(5). Recently, human bocavirus (HBoV) was identified as a cause of human respiratory tract infections in Sweden (6).…”
mentioning
confidence: 99%